Wright’s Nutrush: An Invader of Seasonal Wetlands in Florida - Colette C. Jacono; Kenneth A. Langeland; Jeffrey Hutchinson (EDIS)
This non-native sedge has been increasing in Florida wetlands. This revised 9-page fact sheet describes its distribution, history and impacts, ecological overview, integrated management and identification. Written by Colette C. Jacono, Kenneth A. Langeland, and Jeffrey Hutchinson, and published by the UF Department of Agronomy, November 2011.